The Effect of Company Size, Company Age, Leverage, and Profitability on Earnings Management (Study of Manufacturing Companies Listed on the Indonesia Stock Exchange 2019-2022) - Wilda Fronica Tamba; Yanty Sihotang; Purnama Yanti Purba; Siswanto Siswanto (International Journal of Economics, Business and Innovation Research, 2024)
Negotiation The purpose of this study is to test the effect of company size, company age, leverage, and profitability on profit management (study conducted on manufacturing companies listed on the Indonesian Stock Exchange in 2019-2022). This study uses a quantitative descriptive method. The sampling technique used is purposive sampling, with 80 samples of companies that meet the criteria in this study. The analysis used is linear regression analysis. The results of the study are that age of the company does not have a positive and significant effect on profit management in manufacturing companies listed on the Indonesian Stock Exchange in 2019- 2022. Company size, leverage, and profitability have a positive and significant effect on profit management in manufacturing companies listed on the Indonesian Stock Exchange in 2019-2022. Simultaneously, company size, age, leverage, and profitability as moderating variables have a positive and significant effect on profit management in manufacturing companies listed on the Indonesian Stock Exchange in 2019-2022.